MANAJEMEN OPERASIONAL DI PELABUHAN NUSANTARA KENDARI - Werweti Werweti; Tjuk Sukardiman; Adenan Suhalis (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of this study was to determine the relationship of operational management and service to customer satisfaction in the port of the archipelago Kendari. To collect the data, this study used a questionnaire method / inquiry tangible items of questions. This questionnaire distributed to companies who become customers Kendari port of the archipelago. The population in this study is the customer service users Nusantara Port Kendari. Testing the quality of the data using validity and reliability test and classical assumption. While the analysis model used in this study using multiple linear regression analysis, T test, F test, test the coefficient of determination. The results showed that: 1. In the individual variable operational management and service a significant effect on customer satisfaction in the port of the archipelago Kendari. T test results gained tcount accepted at significance level of 5%; 2. Taken together operational management and service variables significantly influence customer satisfaction in the port of the archipelago Kendari. F assay results received grades of F = 97.224 accepted at significance level of 5%; 3. The operational management of the dominant influence on customer satisfaction, compared to the variable service. T-test results for the variable gain tcount operational management (11.055) higher than the variable tcount services (9.913) at the 5% significance level.